Analysis of Factors Influencing Tourist Satisfaction in the Gedungsongo Temple Area, Semarang Regency - SARUMAHA, Kasdim; PRANOTO, Pranoto (Journal of Tourism Economics and Policy, 2025)
The purpose of the study was to determine and analyze the effect of promotion and facilities on tourist satisfaction in the gedungsongo temple area, Semarang Regency. The research was conducted in the gedungsongo temple area, Semarang Regency. Research using quantitative methods with survey research types. The research population is the tourists of gedungsongo temple in Semarang regency which amounted to 1240 people. The sampling technique is porposive sampling with a sample size of 93 people. The data collection technique is distributing questionnaires while the data analysis technique is multiple linear regression analysis. The results of the study are 1) Promotion has a significant and positive influence on visitor satisfaction with a tcount value of 3.818> t table 1.98638 and a significant value of 0.000 less than 0.05 (sig (0.000) <0.05), 2) Facilities have a significant and positive influence on visitor satisfaction with a tcount of 6.583> ttable 1.98638 and a significant value of 0.000 smaller than 0.05 (sig (0.000) <0.05), 3) Promotion and facilities have a simultaneous influence on visitor satisfaction with a value of Fcount 63,730> Ftable 3.95 with a significant value of 0.000 smaller than 0.05 (0.000 <0.05).